Effectiveness of Gait Training Using Dynamic Bodyweight Support System on Locomotor Abilities of Ambulatory Children With Different Neural Disorders: Gait training in CP children using DBWSS - Zeinalzadeh, Afsaneh; Lotfi, Reza; Barmaki, Hasan; Lotfi, Mohammad; Shadman, Alireza; Asadi, Ali; Kobravi, Hamid Reza (International Clinical Neuroscience Journal, 2023)
Background: In this study, we evaluated the efficacy of dynamic bodyweight-supported training on the gait quality of children with different neural disorders. Methods: Seventeen ambulatory children, aged 3 to 11 years, experiencing gait limitations, were selected to participate in the designed gait training program. Each child participated in 10 practice sessions held three days a week, with each training session using the dynamic body weight support system, comprising three stages, and lasting 20 minutes. Clinical assessments were conducted using four functional tests: “Five Time Sit to Stand Test (FSST)”, “Modified Time Up and Go (MTUG)”, “Time Up and Down Stairs (TUDS)”, and “Pediatric Berg Balance Scale” (BBS). Results: Statistical tests demonstrated a significant increase in the post-values of the BBS after gait training. Notably, children with higher relative cognitive abilities showed more improvement. Additionally, there was a significant enhancement in the assigned score for the level of independence. As all participants had received conventional physical therapies for more than three years, reaching their maximum obtainable improvements with conventional training methods, the observed improvements could be attributed to the designed training protocol even without a control group. Conclusion: Designed gait training protocol using a dynamic weight support system proved effective in enhancing balance, improving gait quality, and increasing the level of independence during performing functional tests in ambulatory children suffering from different locomotor disabilities.